Correlation of force sense error test measured by a pressure biofeedback unit and EMG activity of quadriceps femoris in healthy individuals. (December 2019) - Turkmen, Ceyhun; Harput, Gulcan; Kinikli, Gizem Irem; Kose, Nezire; Guney Deniz, Hande
Abstract: Background: Our study developed a force sense error test (FSET) method for use on the quadriceps muscle, which could be employed in clinical practice to correlate the results of quadriceps muscle activity levels determined by surface electromyography (sEMG). Methods: Twenty-four healthy individuals were included in the study. A pressure biofeedback unit (PBU) placed under the knee joint, was used for force sense error test (FSET) evaluation. First, a maximum contraction value was determined with the PBU. Next, 50% and 65% of the maximum contraction value were used for the analysis. Concurrently, norm values for the quadriceps muscle activity levels were determined by sEMG. Simultaneously, quadriceps muscle activity levels were recorded while testing the FSET using the PBU. Each measurement was repeated in triplicate, and the average constant errors observed by the PBU were recorded in mmHg. Results: The FSET for both 50% and 65% of the normal mmHg value determined using the PBU positively correlated with activity change levels in the quadriceps muscle determined by sEMG (p < 0.05). Conclusions: The relationship between the FSET measured using PBU and changes in the level of activity in the quadriceps muscle showed that a PBU can be used in clinical practice for proprioceptive evaluation of the knee region.